2014
DOI: 10.1177/0164027513520557
|View full text |Cite
|
Sign up to set email alerts
|

Possible Selves and Depressive Symptoms in Later Life

Abstract: The pursuit of personal goals has been linked to general psychological well-being; however, less is known about the association with depression in later adulthood when individuals are contending with age-related changes in health and social relationships. We explored the connection between both health- and social related goals (as measured by possible selves) and depressive symptoms in a sample of 85 community-dwelling older adults who ranged in age from 60 to 92 (M = 74, standard deviation = 7.5). Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…30 More specifically, self-relevant processes can influence goal construction and goal pursuit (eg, hope). [38][39][40] In sum, based on an integration of the main effect model of social support 29 and self-regulation theory, 30 the current study assumes that perceived social support can influence depressive symptoms in two ways. On the one hand, perceived social support has a direct impact on depressive symptoms.…”
Section: The Background Of Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…30 More specifically, self-relevant processes can influence goal construction and goal pursuit (eg, hope). [38][39][40] In sum, based on an integration of the main effect model of social support 29 and self-regulation theory, 30 the current study assumes that perceived social support can influence depressive symptoms in two ways. On the one hand, perceived social support has a direct impact on depressive symptoms.…”
Section: The Background Of Theoretical Frameworkmentioning
confidence: 99%
“…30,56 Individuals' ideas about what they want to be in the future can influence the process of goal construction, which enables individuals to concentrate on their goals and take effort to narrow the discrepancy between their current selves and ideal future selves. 30,37,38 The clear self-concept (eg, future work self) promotes individuals in a positive motivational state to strive for their goals, which also indicates high levels of hope. 39,40 Additionally, a survey has revealed that higher levels of family cohesion, that is, the more love and assistance students receive from their family, the clearer their self-concept is, which promotes the development of hope, and then improves subjective well-being.…”
Section: The Mediation Roles Of Future Work Self and Hopementioning
confidence: 99%
“…As a person navigates age-related changes, there are threats to being able to achieve a hoped-for self or avoid a feared self. Yet, being able to act in accordance with one’s possible selves is vital to adjusting well to developmental changes (Bolkan et al, 2015; Hoppmann et al, 2007). As such, how capable someone feels in achieving and/or avoiding their possible selves could offer a frame of reference against which to frame their SPA.…”
Section: Introductionmentioning
confidence: 99%